Simultaneous Estimation of Lamivudine and Tenofovir Disoproxil Fumarate by RP-HPLC in the Pharmaceutical Dosage Form - Jayadev, S.; Manikanta, K.; Syama Sundar, B.; Jayathirtha Rao, V. (Asian Journal of Chemistry, 2010)
A high performance liquid chromatographic method was developed and validated for the simultaneous quantitative estimation of two antiretroviral drugs viz. lamivudine and tenofovir disoproxil fumarate in tablet dosage form. Chromatography was carried on Agilent eclipse XDB-C18 (5 μm, 4.6 mm × 150 mm) column with mobile phase based comprising of methanol and potassium di-hydrogen orthophosphate (0.02 M) in the ratio 60:40 v/v adjusted to pH 3.0 with formic acid. The flow rate was adjusted to 0.9 mL /min with UV detection at 260 nm. The retention times of lamivudine and tenofovir were found to be 1.9 and 3.4 min, respectively. The different analytical parameters such as linearity, precision, accuracy, ruggedness and robustness, limit of detection and limit of quantification were determined according to the International Conference on Harmonization (ICH) Q2B guidelines. The detector response is linear from 5-50 μg/mL for both lamivudine and tenofovir. The proposed method is highly sensitive, precise and accurate and hence was successfully applied for the reliable quantification of active pharmaceutical present in the commercial formulations.